A SATISFAÇÃO COM O ENSINO PÚBLICO NO MUNICÍPIO DE HORIZONTINA - JUNG, CÉLIO; MARIN, CLÁUDIO; RODRIGUES, GUILHERME; FRANKE, TIAGO M.; ZAMBERLAN, LUCIANO; SOARES, JÚLIO C. V. (Salão do Conhecimento, 2013)
Resumo